A java servlet based transaction broker for internet of things edge device communications - Zainatul Yushaniza Mohamed Yusoff; Mohamad Khairi Ishak; Lukman AB Rahim (Bulletin of Electrical Engineering and Informatics, 2022)
Internet of things (IoT) technology is growing exponentially in almost every sphere of life. IoT offers several innovation capabilities and features, but they are also prone to security vulnerabilities and risks. These vulnerabilities must be studied to protect these technologies from being exploited by others. Cryptography techniques and approaches are commonly used to address and deal with security vulnerabilities. In general, the message queuing telemetry transport (MQTT) is an application layer protocol vulnerable to various known and unknown security issues. One possible solution is to introduce an encryption algorithm into the MQTT communication protocol for secure transmission. This study aims to solve the security problem of IoT traffic by using a secure and lightweight communication proxy. The strategy behind this communication broker acts as a network gateway providing secure transaction keys to all IoT nodes in the network. This task uses a java servlet and elliptic curve cryptography (ECC) algorithm to generate identity encryption keys in a component-based web transaction infrastructure. This approach encrypts the data before it is sent via the MQTT protocol to secure the communication channel and raise the security device and network transactions.